Impacts of human disturbances on habitat use by the Malayan leopard in a fragmented secondary forest, Malaysia. - Sanei, Arezoo (2011)
Very little is known about the leopard (Panthera pardus) in Malaysian tropical rainforests, particularly in a human-dominated and highly fragmented habitat after incidence of rapid deforestations. The objective of this study was to understand the impacts of disturbance factors on the leopard habitat use in a highly fragmented forest within Malaysia's capital agglomeration. We collected detection/non-detection data for leopards, four anthropogenic factors namely construction, deforestation, plantation and settlements and one feral species (i.e. stray dog) from February 2008 for duration of 13 months. We used Jacob's preference Index to examine the effect of human disturbance factors on leopard presence/absence in various parts of the study area. Spearman Correlation Coefficient was used to examine the possible correlation between presence of stray dogs and leopards. Jacob's preference index demonstrates leopards prefer forested areas rather than more open environments in the vicinity. Furthermore, most ignorance of leopards was shown to the construction activities have taken place in the study area. In contrast, northern parts of the forest with less human factors are mostly preferred by the species. Pearson's correlation coefficient showed a highly negative significant correlation between the presence of leopards and stray dogs in the transect lines. Since leopards are the top predators of this fragmented forest, this study could be used to promote practices of sustainable conservation and environmentally friendly forest management.